TRANSPARENT FINANCIAL ARCHITECTURE AS A TOOL FOR FEDUCING GRAUD RISKS - Lavrik, Natalia (Global Prosperity, 2026)
Abstract. The article is devoted to the study of transparent financial architecture as a tool for reducing fraud risks in the activities of enterprises. The purpose of the study is to substantiate approaches to building a Clear Finance Architecture based on the integration of ERP automation and corporate policies in order to reduce fraud risks in the activities of the enterprise. In the course of the scientific study, general scientific methods of cognition were used: analysis, synthesis, induction, deduction, modeling, generalization and a systems approach. The results of the study show that building a transparent financial architecture at the enterprise involves the structural integration of five key components: strategic positioning of finance, process integration and automation (based on ERP systems), data and analytics, technological basis (AI, ML, blockchain) and a control and risk management system. The emphasis is on creating a single information environment for financial and operational data, which contributes to the centralization of accounting, elimination of fragmentation of information flows and automation of basic control procedures. Special attention is paid to the use of advanced analytics and intelligent tools in ERP systems, which provide for the detection of anomalies and atypical transaction patterns, and also contribute to the transition from periodic control to continuous monitoring of financial risks. The importance of implementing formalized corporate policies, internal control, audit systems and harmonizing the use of ERP with the principles of corporate governance is determined. It is studied that risk management should include assessing vulnerable areas, regularly updating control procedures and training personnel in detecting and preventing fraud. It is concluded that the synergy of ERP, analytics, technologies and internal policies forms a holistic financial architecture focused on preventing financial abuse and increasing transparency, which forms the practical significance of the study through the formation of a methodological basis for building an effective automated financial system of the enterprise.